O ritornelo do horror em Milton Hatoum - Bottos Júnior, Norival (2018)
This study seeks to reflect on the theme of postcolonial horror in the Amazon region and understand it as a fundamental aesthetic-political category in Milton Hatoum's four early novels as a crucial category in the early four novels of Milton Hatoum, Relato de um Certo Oriente (2014), Dois Irmãos (2007), Órfãos do Eldorado (2008) e Cinzas do Norte (2012). The main goal of this research is to understand how the impression of horror becomes inseparable from the ills of the contemporary Amazonian world. According to Luiz Costa Lima (2003), the origin of modern horror refers to the European colonial expansion in the African and Asian continents from the sixteenth century until it reached the shores of the American continent, precipitating to the modern man, victim of colonial and postcolonial exploitation, into the abyss from which he can not return anymore. Epistemologically the horror could be considered an inseparable part of the experience of mankind born in the marginalized regions of the world, including the marginalized of the West itself. We analyze in this thesis three fundamental aspects of modern horror considered fundamental and that are connected in the formation of the ritornello, be it in terms of territory, deterritorialization and reterritorialization, physical or in existential terms: the resonances of the colonial adventure on the African continent reflected in the works of Joseph Conrad, especially the novel In the Heart of Darkness (2010), which prefigures the foundations of the horror of postcolonial extraction that will be reflected in the works of authors appearing in the peripheral regions of the Western world, as seems to be the case of the Amazonian writer Milton Hatoum; the role of the "minor writer", a term coined by Gilles Deleuze (2014), and which concerns the political status of the writer who must assume the role in resisting the petrified image of authoritarian forms of domination through official language, is also discussed to the writer of the margins to sabotage and to destabilize the discourse of the colonizer, breaking with its political and cultural precepts. Finally, it is reflected on the extreme figure of the horror, namely, the image of the narrator who must rescue the past and the memory through the use of the witness, an interval figure, present and absent at the same time, the one who has to report what , however, belongs to the unspeakable, the experience of the unheard and silence, the supreme requirement of the narrators in Milton Hatoum reside in this ambiguous task, the obligation to report what can not in any way be said, the memory of the narrators becomes insufficient in the task of salvaging the debris of the past the Amazonian world that disappeared. This idea refers to the concept of ritornello proposed by Gilles Deleuze and Félix Guattari (2011) and meaning a return without return of a ruined cycle that, however, does not come to an end. As a methodology, we use bibliographical research, especially the epistemological current that is part of the so-called philosophy of the difference, such as Jacques Derrida (2005), Edward W. Said (2009), Michel Foucault (2010), Giorgio Agamben (2008), Gilles Deleuze and Félix Guattari (2011). Among the possible conclusions, we observe that in these four novels dealing with a recent historical period in the history of the Amazon, they constitute a true cartography of the physical and psychic violence perpetrated by the successive waves of European colonization and exploration in the region. It was also possible to conclude that the way the region stood against oppression was by way of silence, an instrument of resistance capable of transforming even memory into an intriguing system of ruins. The last conclusion is that the narrators are not able to carry through to the final form of the testimony of destruction and violence of the horror. Witnessing in this case means witnessing to the limitless experience of the unspeakable.